Effect of Repeated Frying of Potato Chips on Physiochemical Properties of Different Frying Oils and Its Sensory Evaluation - Rabin Poudel; Bishal Thagunna; Bishal Bhattrai; Sushan Subedi; Nishal Baral (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Deep frying involves submerging food in heated oil at about 180°C. Throughout the deep-frying process, various chemical reactions occur, leading to alterations in the physicochemical characteristics of the oil, which can ultimately have detrimental health impacts on consumers. Nevertheless, for reasons of economic efficiency, both home and industrial users frequently reuse cooking oils for deep frying. Consequently, this research aimed to evaluate the physicochemical and nutritional properties of commercially available mustard oil, sunflower oil, soybean oil, and palm oil, in addition to investigating how the repeated deep frying of potato tubers affects the physicochemical and nutritional qualities of the analyzed oil samples. Consequently, the ideal amount of frying cycles for every type of oil was explored. To accomplish this, potato was fried individually using coconut, palm, and sunflower oils over four successive frying cycles. Results revealed that increasing the frying counts resulted in increased peroxide value, acid value, viscosity and refractive index, whereas decrease in moisture, iodine value and DPPH value of four oil samples. The peroxide value (PV) and acid value of mustard oil, sunflower oil, soybean oil, and palm oil showed increases ranging from 1.82 to 7.98 meq/Kg, 5.19 to 11.69 meq/kg, 4.81 to 9.89 meq/kg, and 2.49 to 11.08 meq/kg respectively, with acid values shifting from 1.24 to 6.74 mg KOH/g, 0.17 to 0.49 mg KOH/g, 0.25 to 0.42 mg KOH/g, and 0.80 to 2.86 mg KOH/g. The viscosity increased from 183.33 to 615.09 mPA s, 51.66 to 405.49 mPA s, 165.57 to 590.17 mPA s, and 376.42 to 711.43 mPA s of mustard oil, sunflower oil, soybean and palm oil respectively, while the refractive index increased from 1.4654 to 1.4672, 1.4668 to 1.4710, 1.467 to 1.4722, and 1.4552 to 1.4610 of mustard, sunflower, soybean and palm oil respectively. In contrast, there was a reduction in moisture content, iodine value, and DPPH value for mustard, sunflower, soybean, and palm oil, ranging from 0.16-0.06%, 0.09-0.03%, 0.11-0.04%, and 0.21-0.09%, respectively. The findings indicate that the iodine values decreased from 106.2-88.6 g, 126.2-106.5 g, 129.4-108.4 g, and 54.3-31.82 g, respectively. The DPPH values of oil samples were 63.25%, 72.08%, 82.55%, and 78.18%, respectively. Following the fourth frying cycle, these values dropped to 47.85%, 53.79%, 79.62%, and 69.58%. Higher sensory scores regarding overall acceptability were obtained by chips fried in palm oil and lower by mustard oil.